2018
DOI: 10.1038/s41598-018-31541-z
|View full text |Cite
|
Sign up to set email alerts
|

The recombinase Rad51 plays a key role in events of genetic exchange in Trypanosoma cruzi

Abstract: Detection of genetic exchange has been a limiting factor to deepen the knowledge on the mechanisms by which Trypanosoma cruzi is able to generate progeny and genetic diversity. Here we show that incorporation of halogenated thymidine analogues, followed by immunostaining, is a reliable method not only to detect T. cruzi fused-cell hybrids, but also to quantify their percentage in populations of this parasite. Through this approach, we were able to detect and quantify fused-cell hybrids of T. cruzi clones CL Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 69 publications
4
32
0
1
Order By: Relevance
“…We have described previously that distinct responses to DSBs, through homologous recombination, observed in different T. cruzi DTUs are related to their variable TcRAD51 transcription levels (Alves et al, 2018). Then, in order to verify if there is a direct relation between TcRAD51 mRNA levels and the rate of arrested cells in the strains studied here-Dm28c, Y, CL Brener, and Bug-we performed a qRT-PCR assay to determine the TcRAD51 transcription levels.…”
Section: Rad51 Mrna Levels Are Directly Correlated With Dormancy In Tmentioning
confidence: 98%
See 2 more Smart Citations
“…We have described previously that distinct responses to DSBs, through homologous recombination, observed in different T. cruzi DTUs are related to their variable TcRAD51 transcription levels (Alves et al, 2018). Then, in order to verify if there is a direct relation between TcRAD51 mRNA levels and the rate of arrested cells in the strains studied here-Dm28c, Y, CL Brener, and Bug-we performed a qRT-PCR assay to determine the TcRAD51 transcription levels.…”
Section: Rad51 Mrna Levels Are Directly Correlated With Dormancy In Tmentioning
confidence: 98%
“…Homologous recombination and TcRad51 also play a relevant role in genetic exchange processes since the overexpression of TcRAD51 is capable of stabilizing hybrid T. cruzi cells. In fact, naturally-hybrid T. cruzi's populations show higher expression of TcRAD51 when compared to the non-hybrid ones (Alves et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In spite of being recently proposed by genomic studies [14,20] meiosis has not been reported for T. cruzi in the laboratory yet. Alternatively, experimental tetraploid or sub-tetraploid hybrids were observed in laboratory conditions [21,22]. The fusion of diploid cells to form a tetraploid and posterior random loss of chromosomes slowly returning to diploidy was proposed as a model to explain genetic exchange in this species [21].…”
Section: Introductionmentioning
confidence: 99%
“…In Trypanosoma brucei, HR factors have been clearly implicated in the directed recombination of Variant Surface Glycoprotein (VSG) genes during host immune evasion by antigenic variation (21), as well as in maintenance of the massive subtelomeric VSG gene archive (22,23). In T. cruzi, HR has been suggested to be a driver of variability in multigene families (24,25) and in cell hybridisation (26). Finally, in Leishmania, HR related factors have been implicated in mediating the formation or maintenance of episomes, which appear to form stochastically, arise genome-wide and have been implicated in acquisition of drug resistance (27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%